DIGITALISASI PARIWISATA BERBASIS WEBSITE DI DESA WISATA PENGLIPURAN BALI - Ni Wayan Rena Mariani; Putu Ryan Dharma Putra; Putu Chindy Laeryancia Devanda; Ivana Putri Sunarto (Jurnal Mantik, 2022)
The rapid development of information technology and the internet has changed various aspects of human life, including drastically changing the tourism industry. In a dynamic global society, the evolution of information technology has become one of the key development factors. This radically changed the world of the tourism industry and offered a new perspective of development. All information related to tourism can be distributed through the use of information technology (Wolah, 2016). That way, tourists can get tourism information with the help of communication and information technology quickly. This research was conducted in Penglipuran Village which is located in Bangli District, Bangli Regency, Bali. The reason for choosing this location is because Penglipuran Village is one of the tourist villages that has a fairly rapid development in Bali and has become a tourist attraction that is very popular with tourists, both local and foreign tourists. This type of research is qualitative which in this study does not focus on numbers or numerics but rather focuses on knowing a phenomenon in depth by using data that has been obtained in the field. Panglipuran Village is one of the tourist villages with a variety of uniqueness. Information about this village is published on a website with the url penglipuran.net. This website is analyzed using 5 dimensions of Destination Management System (DMS). Penglipuran village website fulfills 2 of the 5 dimensions of DMS. In the next development the Penglipuran Village Website can be developed into a dynamic website so that it can fulfill the 5 dimensions of the DMS.